Efecto del desarrollo del pensamiento crítico sobre la gestión educativa ambiental en los tiempos de COVID-19 - Ramos Guillén, Marta Soledad; Evangelista Vargas, Oscar Diego; Pérez Diaz, Vilma; Espinoza Ortiz, Diego Mauricio (Pontificia Universidad Católica del Perú, 2025)
This study examines the relationship between the development of critical thinking and environmental educational management within a secondary-level educational community in Peru, in the context of the COVID-19 pandemic. Employing a mixed-methods approach with a concurrent multilevel design, the research explores how economic, social, and cultural factors influence critical thinking. Through exploratory factor analysis and structural equation modeling, three key dimensions of critical thinking are identified: substantial, contextual, and pragmatic development, with substantial development emerging as the most significant predictor. The findings underscore the importance of pedagogical strategies that enhance both critical and environmental awareness, thereby supporting educational management practices that foster adaptation to emerging environmental and social challenges.

Este estudio analiza la relación entre el desarrollo del pensamiento crítico y la gestión educativa ambiental en una comunidad educativa de nivel secundario en Perú, en el contexto de la pandemia del COVID-19. Con un enfoque mixto y un diseño concurrente a varios niveles, se explora la influencia de factores económicos, sociales y culturales en el pensamiento crítico. Mediante análisis factorial exploratorio y modelos de ecuaciones estructurales se identifican tres categorías clave del pensamiento crítico: desarrollo sustancial, contextual y pragmático; el desarrollo sustancial es el predictor más relevante. Los hallazgos subrayan la importancia de estrategias pedagógicas que fortalezcan la conciencia crítica y ambiental, promoviendo una gestión educativa que facilite la adaptación a los desafíos ambientales y sociales emergentes.

Este estudo analisa a relação entre o desenvolvimento do pensamento crítico e a gestão da educação ambiental em uma comunidade educacional de nível secundário no Peru, no contexto da pandemia de COVID-19. Adotando uma abordagem mista com um delineamento concorrente em múltiplos níveis, investiga-se a influência de fatores econômicos, sociais e culturais sobre o pensamento crítico.Por meio de análise fatorial exploratória e modelagem por equações estruturais, são identificadas três dimensões principais do pensamento crítico: desenvolvimento substancial, contextual e pragmático, sendo o desenvolvimento substancial o preditor mais significativo. Os resultados ressaltam a importância de estratégias pedagógicas que promovam a consciência crítica e ambiental, favorecendo uma gestão educacional capaz de facilitar a adaptação frente aos desafios ambientais e sociais emergentes.
Effect of critical thinking development on environmental educational management in times of COVID-19
Efeito do desenvolvimento do pensamento crítico na gestão da educação ambiental em tempos de COVID-19
Keywords: Critical thinking development; Environmental educational management; Socioeconomic factors; Factor analysis; COVID-19; Desarrollo del pensamiento crítico; Gestión educativa ambiental; Factores socioeconómicos; Análisis factorial; COVID-19; Desenvolvimento do pensamento crítico; Gestão da educação ambiental; Fatores socioeconômicos; Análise fatorial; COVID-19; https://purl.org/pe-repo/ocde/ford#5.03.00